Promising horizons in achondroplasia along with the development of new drugs - Keiichi Ozono; Takuo Kubota; Toshimi Michigami (Endocrine Journal)
Achondroplasia (ACH) is a representative skeletal disorder characterized by rhizomelic shortened limbs and short stature. ACH is classified as belonging to the fibroblast growth factor receptor 3 (FGFR3) group. The downstream signal transduction of FGFR3 consists of STAT1 and RAS/RAF/MEK/ERK pathways. The mutant FGFR3 found in ACH is continuously phosphorylated and activates downstream signals, resulting in abnormal proliferation and differentiation of chondrocytes in the growth plate and cranial base synchondrosis. A patient registry has been developed and has contributed to revealing the natural history of ACH patients. Concerning the short stature, the adult height of ACH patients ranges between 126.7–135.2 cm for men and 119.9–125.5 cm for women in many countries. Along with severe short stature, foramen magnum stenosis and spinal canal stenosis are major complications: the former leads to sleep apnea, breathing disorders, myelopathy, hydrocephalus, and sudden death, and the latter causes pain in the extremities, numbness, muscle weakness, movement disorders, intermittent claudication, and bladder-rectal disorders. Growth hormone treatment is available for ACH only in Japan. However, the effect of the treatment on adult height is not satisfactory. Recently, the neutral endopeptidase-resistant CNP analogue vosoritide has been approved as a new drug for ACH. Additionally in development are a tyrosine kinase inhibitor, a soluble FGFR3, an antibody against FGFR3, meclizine, and the FGF2-aptamer. New drugs will bring a brighter future for patients with ACH.